2019
DOI: 10.4103/ijpvm.ijpvm_485_18
|View full text |Cite
|
Sign up to set email alerts
|

Overcoming challenges of implementing chronic care model in diabetes management: An action research approach

Abstract: Background: Reforming the health care system to improve suitable health care model for diabetic patients is essential. This study aimed to implement, identify, and overcome the challenges of implementing the Chronic Care Model in diabetes management in a clinic. Methods: This study is a qualitative technical action research with the Kemmis and McTaggart model including planning, action, reflection, observation, and revision plan which was conducted in the specialized po… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(3 citation statements)
references
References 11 publications
(14 reference statements)
1
2
0
Order By: Relevance
“…The literature suggests that the successful implementation of the CCM provides health professionals an effective framework for supporting diabetes self-management [ 27 ]. In line with previous studies [ 28 , 29 , 30 , 31 ], our findings showed that the self-management and delivery system design components of CCM are promising in diabetes management in the context of primary healthcare of Pakistan.…”
Section: Discussionsupporting
confidence: 91%
“…The literature suggests that the successful implementation of the CCM provides health professionals an effective framework for supporting diabetes self-management [ 27 ]. In line with previous studies [ 28 , 29 , 30 , 31 ], our findings showed that the self-management and delivery system design components of CCM are promising in diabetes management in the context of primary healthcare of Pakistan.…”
Section: Discussionsupporting
confidence: 91%
“…Regarding that the main focus in codification necessary competencies to manage diabetes is making a structure to provide minimum needed knowledge, skills and capabilities in practice in every levels of diabetes wide cares. [ 9 ] Many studies also emphasized lack of knowledge and widespread and serious lack of knowledge of educators about methods and techniques of education and care according to the needs of patients[ 8 10 11 12 ]…”
Section: Introductionmentioning
confidence: 99%
“… 7 , 8 Early diagnosis, prompt clinical care, and patient counselling and empowerment through education are the most crucial steps in DM management because they help lower the risk of DM-related complications and help affected individuals to sustain good quality of life. 9 , 10 Easy access to primary healthcare settings that deliver cost-effective interventions for individuals with DM can improve their outcomes. These interventions include a combination of diet, physical activity, medication; and regular screening for complications, which aims to first achieve adequate control of blood glucose and subsequently prevent further complications.…”
Section: Introductionmentioning
confidence: 99%